Penambahan bht pada produk desiccated coconut medium grade subkultivar kelapa dalam watulimo - Waqif Agusta; Wendianing Putri Luktesi; Kresna Mulya Santosa; Muhammad Nur Kholis; Mokhammad Rizqi Tobibi Herman; Alief Fathin Nurrochman; Lusiana Kresnawati Hartono; Indah Kurniasari; Mohammad Nafila Alfa (AGROINTEK, 2025)
Coconut holds immense significance in Indonesian coastal communities, offering diverse benefits from its fruit, leaves, trunk, and roots. It plays a pivotal role in the local economy, particularly in East Java's Trenggalek region, a significant coconut producer. In 2021, Trenggalek, notably Watulimo District, contributed significantly to the national coconut production. Desiccated coconut, a vital processed product, was studied concerning temperature and adding BHT (Butylated hydroxytoluene). The research aimed to assess their impacts on desiccated coconut properties. Conducted through various tests, including yield, pH, water activity, phenol content, and organoleptic evaluations, the study utilized a Completely Randomized Design (CRD). Based on the research findings, BHT (Butylated hydroxytoluene) significantly influences the quality of desiccated coconut, with values of 0.38 for water activity response and 0.36 mgGAE/g for total phenol content response. Drying temperature treatment affects the quality parameter value, with a yield response of 65.02 %. The pH value of desiccated coconut remains within the normal range, ranging from 6.33 to 6.44. The optimal treatment is found at a temperature of 80°C and the addition of 0.347 g of BHT to produce the best medium-grade desiccated coconut.